Phosphodiesterase 4 mediates interleukin‐8‐induced heterologous desensitization of the β2‐adrenergic receptor. Issue 10 (23rd September 2021) - Rich, Thomas C.; Leavesley, Silas J.; Brandon, Angela P.; Evans, Cilina A.; Raju, S. Vamsee; Wagener, Brant M.
Abstract: Acute respiratory distress syndrome (ARDS) is a life‐threatening illness characterized by decreased alveolar‐capillary barrier function, pulmonary edema consisting of proteinaceous fluid, and inhibition of net alveolar fluid transport responsible for resolution of pulmonary edema. There is currently no pharmacotherapy that has proven useful to prevent or treat ARDS, and two trials using beta‐agonist therapy to treat ARDS demonstrated no effect. Prior studies indicated that IL‐8‐induced heterologous desensitization of the beta2‐adrenergic receptor (β2 ‐AR) led to decreased beta‐agonist‐induced mobilization of cyclic adenosine monophosphate (cAMP). Interestingly, phosphodiesterase (PDE) 4 inhibitors have been used in human airway diseases characterized by low intracellular cAMP levels and increases in specific cAMP hydrolyzing activity. Therefore, we hypothesized that PDE4 would mediate IL‐8‐induced heterologous internalization of the β2 ‐AR and that PDE4 inhibition would restore beta‐agonist‐induced functions. We determined that CINC‐1 (a functional IL‐8 analog in rats) induces internalization of β2 ‐AR from the cell surface, and arrestin‐2, PDE4, and β2 ‐AR form a complex during this process. Furthermore, we determined that cAMP associated with the plasma membrane was adversely affected by β2 ‐AR heterologous desensitization. Additionally, we determined that rolipram, a PDE4 inhibitor, reversed CINC‐1‐induced derangements of cAMP and also caused β2 ‐AR to successfully recycle back to the cell surface. Finally, we demonstrated that rolipram could reverse CINC‐1‐mediated inhibition of beta‐agonist‐induced alveolar fluid clearance in a murine model of trauma‐shock. These results indicate that PDE4 plays a role in CINC‐1‐induced heterologous internalization of the β2 ‐AR; PDE4 inhibition reverses these effects and may be a useful adjunct in particular ARDS patients.